Pengukuran Lahan Sekolah Untuk Mendukung Penataan Lingkungan Di SMA Negeri 1 Gunungsitoli Idanoi - Dermawan Zebua; Hamedoni Harita; Envilwan Berkat Harefa; Ayler Beniah Ndraha; Ofelius Laia; Ikhtiar Aronifati Daeli; Muhammad Haris Zalukhu; Jurisman Waruwu; Jun Fajar Krisman Giawa; Kevin Berkat Mendrofa; Friski Dermawan Zebua; Rifki Wahyudi Mendrofa (CV. SINAR HOWUHOWU, 2025)
This Community Service Program (Pengabdian kepada Masyarakat/PKM) aimed to support school environmental planning through land measurement activities at SMA Negeri 1 Gunungsitoli Idanoi. The main problem faced by the partner school was the absence of accurate and well-documented land measurement data to serve as a basis for environmental arrangement and infrastructure planning. The implementation method consisted of several stages, including coordination with school stakeholders, technical preparation, direct land measurement in the field, data processing, and the formal handover of measurement results to the school. The program applied a participatory approach by involving school representatives during the measurement process as a form of technical assistance and knowledge transfer. The results showed that the land measurement activities successfully produced systematic and reliable data on land area and spatial division, which can be utilized as a foundation for school environmental management and future infrastructure development. In addition, the activity enhanced the school’s understanding of the importance of spatial data in educational environment planning. Therefore, this community service program provided practical and sustainable benefits for the school and strengthened the role of higher education institutions in supporting the improvement of educational environments.